(3GddeMGJ GdQGaYGJ ddJOgjT Yf eYGfi UdhGJ GHf eTjTs - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdUdGI hGdJSdje Ydi MHjHg HGHkG ehUdkG Edi ONhd OGQ GdfYje hHYO ajbhd CjbXfi GdMb SfI Cda heGFI hSHYI hKdGKjf acGfJ SGYI eHGQcI hSejJg s
(3BNQgG (B:s
(3ai HMGQ GdfOGhGf dGJTeJ HfG GdYOGhGf hCf JLYdfG eef EgJOG hgOG hUdi Gddg JYGdi hSde Ydi SjOfG eMeO hYdi Bdg hCUMGHg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH GdeJf HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs